A wideband, compact, high gain, low-profile, monopole antenna using wideband artificial magnetic conductor for off-body communications. Issue 2 (20th March 2022) - Hazarika, Bidisha; Basu, Banani; Nandi, Arnab
Abstract: A wideband staircase pattern defected ground monopole antenna integrated with an artificial magnetic conductor (AMC) reflector has been proposed for C-band (4–8 GHz) and ITU band (8.01–8.5 GHz) applications. The integrated antenna consists of a staircase antenna at top, a 2 × 2 AMC reflector at the bottom and an air substrate as gap between them. The AMC offers 18.5% ± 90° reflection phase bandwidth from 6.10 to 7.32 GHz. The AMC layer has achieved mu-negative properties in the designated band. The AMC proffers polarization independent behavior in the respective frequency band depicting robustness in AMC reflection phase characteristics. The integrated antenna has offered a wide impedance bandwidth of 2.78 GHz (42.8% at 6.5 GHz and 34.1% at 8.15 GHz) due to the defected ground monopole. The integration of wideband AMC beneath the staircase monopole antenna alters the out of phase radiation to in-phase planer pattern which enhances the peak gain up to 9.7 dB. It reduces the 1-g averaged specific absorption rate to 0.223 and 0.324 W/kg at the two designated bands. The structure maintains almost similar bandwidth and gain due to artificial human body loading.